2005
DOI: 10.1111/j.1440-1797.2005.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of pulse intravenous cyclophosphamide versus mycophenolate mofetil in the induction therapy of proliferative lupus nephritis

Abstract: MMF in combination with corticosteroids is an effective induction therapy for moderately severe proliferative lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 19 publications
5
167
1
5
Order By: Relevance
“…Evidence from early observational studies suggested that MMF may be efficacious in inducing remission of lupus nephritis (8 -11). More recently, randomized, controlled trials (RCT) comparing MMF and cyclophosphamide as induction agents in lupus nephritis have also been completed (12)(13)(14)(15) with similar results. Conclusions based on these trials, however, are limited given their small sample sizes.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Evidence from early observational studies suggested that MMF may be efficacious in inducing remission of lupus nephritis (8 -11). More recently, randomized, controlled trials (RCT) comparing MMF and cyclophosphamide as induction agents in lupus nephritis have also been completed (12)(13)(14)(15) with similar results. Conclusions based on these trials, however, are limited given their small sample sizes.…”
mentioning
confidence: 64%
“…The mean age of patients ranged from 28 to 42 yr, with most patients of female gender (range 79 to 94%). The most common ethnic group was Asian (18), and three RCT compared MMF with intravenous cyclophosphamide (13,14,19). Dosing of MMF varied across studies, ranging from 1 to 3 g/d.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have showed that CYC may cause leukopenia, thrombocytopenia, and erythropenia. The WBC count showed a saw-tooth pattern with IV CYC as it reached a nadir approximately 2 weeks following administration [24]. Our data showed that the SILD IV CYC would keep the WBC counts at relatively low levels.…”
Section: Discussionmentioning
confidence: 55%
“…MMF is a drug which usually is well tolerated. In patients with auto-immune diseases such as SLE, MMF is effective in inducing remission with short-term efficacy which is comparable with cyclophosphamide (Chanet al, 2000(Chanet al, , 2005Ong et al, 2005;Ginzler etal., 2005). Induction treatment with MMF and oral steroids consisted of oral MMF 1000 mg twice daily and oral prednisolone 1 mg/kg once daily (maximum 60 mg).…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%